2021
DOI: 10.1186/s13287-021-02382-x
|View full text |Cite
|
Sign up to set email alerts
|

Human amnion-derived mesenchymal stem cells improved the reproductive function of age-related diminished ovarian reserve in mice through Ampk/FoxO3a signaling pathway

Abstract: Background Age-related diminished ovarian reserve (AR-DOR) reduced the quality of oocytes, resulting in decreased female fertility. Aging is tightly related to abnormal distribution and function of mitochondria, while mitophagy is a major process to maintain normal quality and quantity of mitochondria in cells, especially in oocytes which containing a large number of mitochondria to meet the demand of energy production during oocyte maturation and subsequent embryonic development. Ampk/FoxO3a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 66 publications
0
16
0
Order By: Relevance
“…hAMSCs were prepared in the State Key Laboratory of Reproductive Medicine, The First Affiliated Hospital of Nanjing Medical University, Jiangsu Province Hospital ( Liu et al, 2021b ), a Good Manufacturing Practice (GMP)-compliant laboratory according to the national principle ( ‘Guiding Principle for Cell Therapy Products Research and Assessment Technique’, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…hAMSCs were prepared in the State Key Laboratory of Reproductive Medicine, The First Affiliated Hospital of Nanjing Medical University, Jiangsu Province Hospital ( Liu et al, 2021b ), a Good Manufacturing Practice (GMP)-compliant laboratory according to the national principle ( ‘Guiding Principle for Cell Therapy Products Research and Assessment Technique’, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…6 c), indicating that SOD2 gene transcription was promoted by apoVs treatment. As a result, we looked through transcription factors which can regulate transcription of SOD2 gene according to previous studies, in which we found out FOXO3a (Forkhead box O3) [ 44 ]. The location of FOXO3a in cells depends on its activation state.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the future studies should concentrate on promoting early post-transplantation revascularization and improving fertility associated with age-related declines in oocyte quality. Numerous studies have demonstrated that mesenchymal stem cells (MSCs) could significantly stimulate neovascularization and increase blood perfusion to reduce the loss of primordial follicles [ 15 , 16 ] and effectively improve the quality and number of oocytes in aged mice [ 17 19 ]. This represents a new strategy toward boosting fertility in women with reduced ovarian reserve.…”
Section: Introductionmentioning
confidence: 99%